Photoshop Tutorial Courseware (PTC) / Nurul Dania Anis Mohd Zainon - Mohd Zainon, Nurul Dania Anis (2016)
In this era, technology is essential in teaching and learning process and it influences the subject or course that is taught and enhances student’s learning. Students use computers, Internet, and multimedia resources, more frequently referred to as information and communications technology (ICT). Among its impacts is the advancement of programming and courseware as teaching aids. The use of multimedia courseware in learning and teaching has created a new environment in education sector. Moreover, to develop Photoshop Tutorial Courseware project, ADDIE Model has been choose to use as instruction designer. The developer should follow all the guideline to get success results and the process of development will be easier. Furthermore, 30 questionnaires had been distributed to respondents among students at UiTM Kuala Terengganu. The content of the questionnaire is divided in 2 part which are part A and part B. Meanwhile, part B has 6 categories of construct which are user evaluation on interface design, usability, activities, navigation and element of multimedia. The highest mean between these six construct is construct B with the average mean 4.33 and standard deviation is 0.610.